The Effects of Nanofluids on Forced Convection Heat Transfer Inside Parallel Plate Heated with Flush Mounted Discrete Heater Sources - Atmaca, Ş. Ulaş; Göktepeli, İlker; Ateş, Ali (International Journal of Civil, Mechanical and Energy Science, 2023)
A numerical solution on forced convection of Al2O3-water nanofluid for different volume fractions is investigated for laminar flow through a parallel plate with flush mounted discrete heat sources. The model used for nanofluid mixture is a single-phase approach and fluid properties are considered constant with temperature. The finite difference method is used for solutions and four different volume fractions are considered varying from 0% to 4%. A fully developed laminar velocity profile is considered and the parallel plate is assumed as heated with three discrete heat sources flush mounted to the top and bottom plate with the same lengths. Uniform wall temperature boundary condition is taken for discrete heaters. Peclet numbers are in the range of 20-100. For comparison and validity of the solution the results for a classical problem, laminar flow through a parallel plate which is heated at the downstream region with constant temperature, are obtained. Results are presented in terms of bulk temperature, heat flux, and local Nusselt number. Heat transfer is enhanced with the particle volume concentration. For comparison, pure water results are also shown in the figures. At the locations where heat is applied the heat flux values decrease as the volume fraction increase and the bulk temperature values are higher for the higher volume fractions at the heated locations. As the volume fraction increases the local Nusselt number can increase up to 30% than to pure water.